Corner stores as community hubs: a systematic review of public health, economic impact, and social dynamics in urban areas - Cadavid-Gómez, Hernán Darío; Cano, Jose Alejandro; Sánchez-Torres, Javier A. (Frontiers in Nutrition, 2025)
Corner stores, or neighborhood stores, are small retail spaces prevalent in urban and underserved areas, where they play a critical role in providing convenient access to food, beverages, and other necessities. This systematic review examines the multifaceted role of corner stores, focusing on their impact on public health, community dynamics, and local economies. Through an analysis of key studies, this article explores public health initiatives aimed at improving the nutritional offerings in corner stores, the socio-cultural role these stores play within communities, consumer behavior and purchasing patterns, and the unique business models that sustain them. The findings highlight the potential of corner stores to act as accessible health intervention points, culturally significant spaces, and small but impactful economic drivers in underserved neighborhoods. Despite the potential of corner stores to act as accessible intervention points for healthier eating and community development, challenges such as limited infrastructure and competition from larger retailers remain. Additionally, this systematic review highlights gaps in existing research and suggests future studies that explore long-term public health impacts, economic sustainability, and policy implications to enhance the positive contributions of corner stores to urban communities.